Nonlinear two-field models from orbit equation deformations - De Souza Dutra, A. [UNESP]; Goulart, P. E.D. [UNESP] (American Physical Society (APS), 2011)
In this work, studying systems of two coupled fields in (1+1)D, which present kinklike solutions, we introduce an orbit equation deformation procedure. We apply it in cases which present periodic behavior in the fields potential. We build new periodic potentials using this method. © 2011 American Physical Society.